2019
DOI: 10.1016/j.diabres.2019.107930
|View full text |Cite
|
Sign up to set email alerts
|

Balance, risk of falls, risk factors and fall-related costs in individuals with diabetes

Abstract: Sensory loss and impaired balance are considered risk factors of incident falls. The aim of this study was to assess the relationship between degree of foot sensation and balance, risk of falls, incidence of fall-related injuries and costs in a cohort of patients with diabetes. Methods: (Non)-neuropathic subjects participating in the Rotterdam Diabetic Foot Study were followed prospectively. Subjects underwent sensory testing of the feet (39 item Rotterdam Diabetic Foot Study Test Battery (RDF-39)); balance wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
19
1
2
Order By: Relevance
“…Falls refer to unintentionally falling to the ground or a lower plane, which is the main cause of preventable injuries, even disability and death of the elderly [3].Sibley et al [15] demonstrated that 62% of people who fell had concurrent diseases, such as arthritis, visual impairments, hypertension, chronic obstructive pulmonary disease, diabetes or heart disease, and only 23.8% of them had a single chronic disease.T2DM patients hold a variety of metabolic disorders predisposing to hypertension, dyslipidemia, osteoporosis, ischemic cerebrovascular diseases, poor lower-extremity performance, and dysequilibrium. The risk of falls [13][14] and the proportion of hospitalization due to falls are both higher than non-DM patients [9,10].In our study, the incidence of DN, DR, CKD and CI in patients with T2DM in the fall group during hospitalization was signi cantly greater than that in the nonfall group, further verifying that comorbidity is an signi cant factor for falls [16].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Falls refer to unintentionally falling to the ground or a lower plane, which is the main cause of preventable injuries, even disability and death of the elderly [3].Sibley et al [15] demonstrated that 62% of people who fell had concurrent diseases, such as arthritis, visual impairments, hypertension, chronic obstructive pulmonary disease, diabetes or heart disease, and only 23.8% of them had a single chronic disease.T2DM patients hold a variety of metabolic disorders predisposing to hypertension, dyslipidemia, osteoporosis, ischemic cerebrovascular diseases, poor lower-extremity performance, and dysequilibrium. The risk of falls [13][14] and the proportion of hospitalization due to falls are both higher than non-DM patients [9,10].In our study, the incidence of DN, DR, CKD and CI in patients with T2DM in the fall group during hospitalization was signi cantly greater than that in the nonfall group, further verifying that comorbidity is an signi cant factor for falls [16].…”
Section: Discussionsupporting
confidence: 68%
“…Apart from the sensation abnormality of pain, stress and temperature, DPN also complicates with plant nerve, cranial nerves, central nervous system lesions, leading to proprioceptive hypoesthesia. Besides, the coexistence of Dyslipidemia, hypertension, cerebral infarction withT2DM, the action of diabetic peripheral vascular disease and diabetic microangiopathy, will all intensify balance decline, leading to increased risk of falling due to instability of standing and acting [9,10,14 ].Multi-factorial regression analysis illustrated that cerebral infarction was the main risk factor for falls, and the OR value was as high as 21.738, suggesting that T2DM combined with cerebral infarction signi cantly increased the risk of falls during hospitalization, which was further veri ed by this result. However, due to the small sample size, there was no signi cant correlation with other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Early to advanced stages of (large fiber) sensory loss are assessed, now also resembling ulcer risk. The RDF-39 has been shown to correlate with postural stability and predicts recurrent falls 21 . The primary outcome of the current study was incident DFU occurring in either foot.…”
Section: Discussionmentioning
confidence: 99%
“…The RDF‐39 is a 40‐point scale, ranging from 0 (no aberrant tests) to 39 (all tests aberrant), and includes tests on static and moving two‐point discrimination (S2PD and M2PD, respectively), vibration sense, 10‐g monofilaments, and cold stimuli that are applied on various sites of the feet, supplemented with information on experienced numbness, Romberg test, prior ulceration, and lower‐extremity amputations. A low score on the RDF‐39 represents little deafferentation (ie, sensory loss), while a high score represents severely diminished pedal perception that increasingly relates to risk of DFU development and falls …”
Section: Introductionmentioning
confidence: 99%